2015
DOI: 10.1039/c5nj01597a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium catalyzed decarboxylative acylation of arylboronic acid with ethyl cyanoacetate as a new acylating agent: synthesis of alkyl aryl ketones

Abstract: The versatile, one-pot synthesis of a series of alkyl aryl ketones is described using ethyl cyanoacetate as a new acylating agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 75 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…In line with our earlier observation, 11 we can speculate a plausible mechanism for the aqueous acid mediated domino In summary, we have developed an efficient, one-pot reaction protocol for the addition of diversely substituted arylboronic acids to substituted aliphatic nitriles in aqueous acetic acid medium to provide the synthetically useful 3-carbethoxy/nitrile 2-arylpyrroles. This method generates a pyrrole, leaving the NH, C4/C5 position free for further manipulations.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…In line with our earlier observation, 11 we can speculate a plausible mechanism for the aqueous acid mediated domino In summary, we have developed an efficient, one-pot reaction protocol for the addition of diversely substituted arylboronic acids to substituted aliphatic nitriles in aqueous acetic acid medium to provide the synthetically useful 3-carbethoxy/nitrile 2-arylpyrroles. This method generates a pyrrole, leaving the NH, C4/C5 position free for further manipulations.…”
supporting
confidence: 86%
“…10 In our previous studies, we have shown that ethyl cyanoacetate and substituted ethyl cyanoacetate are useful acyl equivalents for the synthesis of alkyl aryl ketones. 11 In light of this fact, we envisaged that substitution of one of the active methylene protons of ethyl cyanoacetate/malononitrile by an alkyl group bearing a pendent aldehyde function should serve as an ideal substrate for pyrrole synthesis. Nucleophilic addition of an arylboronic acid to the nitrile using a mild acid, such as aqueous acetic acid, should lead to a Paal−Knorr intermediate (intermediate E in Scheme 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of inert C≡N bond activation/carbon-carbon or carbon-heteroatom bond-forming reactions catalyzed by transition metals has attracted significant attention of organic chemists during the past several decades [4]. Since Larock’s pioneering work on the development of the catalytic carbopalladation of nitriles [5,6,7], remarkable progress in the transition metal catalyzed addition of organoboron reagents to nitriles has been documented during the past several decades by several other groups [8,9,10,11] and our group [12,13,14]. In recent years, the scope of this chemistry has been significantly expanded to other coupling partners, including sodium aryl sulfinates or arylsulfinic acids [15,16,17,18], aryl halides [19,20], benzoic acids [21], arylhydrazines [22], and arylsulfonyl hydrazides [23].…”
Section: Introductionmentioning
confidence: 99%
“…Considering its wide application scope for ligand development, pyrazole has been used to replace one of the pyridine rings in bipyridine systems, leading to the formation of organometallic complexes with useful photoelectronic and electrochemical properties . However, the use of such pyrazolopyridine ligands in Pd-catalyzed reactions remains limited to a few examples of cross-coupling reactions . Furthermore, the synthesis of conformationally fixed pyrazolopyridine compounds with fused ring systems and their applications as ligands have not been reported to the best of our knowledge.…”
mentioning
confidence: 99%